Penanaman Pendidikan Tauhid di Taman Kanak-kanak Zahrawain Surakarta, Analisis Ontologi dan Epistimologi Filsafat Islam - Hartanto, Rudy (TSAQOFAH, 2025)
Tauhid education for early childhood is crucial in shaping their belief in God, especially during their formative years. At Tahfidz Zahrawain Kindergarten, Tauhid education is implemented not only through theoretical teaching but also by integrating Tauhid values into daily activities that shape children's lives. This approach combines two aspects of Islamic philosophy: ontology, which teaches about God's existence, and epistemology, which guides children in acquiring knowledge about God through sensory experience and divine revelation. However, teaching the abstract concept of Tauhid to children who are still in a stage of simple cognitive development presents a challenge. Therefore, creative methods that align with children's psychological development are essential, such as learning supplications (du'a), practicing prayer (sholat), and memorizing the Qur'an. These methods help deepen their understanding of Tauhid holistically.